Presenting new language - Hadfield, Jill (Oxford Univ. Press, 2000)
This book contains 30 activities at elementary level, complete with ideas for boardwork and pictures teachers can copy. All the activities are simple and adaptable. They are particularly well-suited to classrooms where there are few resources apart from a board, paper, and pens - and of course the teacher and the learners themselves